Entrepreneurship and well-being: the role of national entrepreneurship norm and the importance of meaningfulness at work - Tavares, S. M.; Carvalho, H.; Santos, S. C.; van Veldhoven, M. (13th European Academy of Occupational Health Psychology Conference: adapting to rapid changes in today’s workplace, 2018)
This study investigates whether entrepreneurship (operationalized as self-employment status) is related to higher levels of meaningfulness at work and individual’s well-being, specifically subjective vitality, when compared to regular employment. We propose that the impact of self-employment on meaningfulness at work would depend on countries’ normative context, namely on the national entrepreneurship prescriptive norm. We analysed 2010’s data from the Global Entrepreneurship Monitor and the European Social Survey on 16 European countries and tested a cross-level moderated mediation model. Results showed that entrepreneurship is positively related to individual’s well-being through the mediating effect of meaningfulness at work. However, the effect of entrepreneurship on individuals’ meaningfulness at work and, ultimately, on their subjective vitality, is stronger for people living in countries with less favorable national entrepreneurship norm. These findings provide evidence for framing meaningfulness at work as being contingent on the interaction between self-employment and national normative context and contribute to the literatures on entrepreneurship, meaningfulness, and well-being at work